2008
DOI: 10.1609/aimag.v29i3.2160
|View full text |Cite
|
Sign up to set email alerts
|

Networks and Natural Language Processing

Abstract: edge types have been used. Text units of various sizes and characteristics can be added as vertices in the graph, for example, words, collocations, word senses, entire sentences, or even entire documents. Note that the graph nodes do not have to belong to the same category. For example, both sentences and words can be added as vertices in the same graph. Edges can represent cooccurrence (such as two words that appear in the same sentence or in the same dictionary definition), collocation (for example, two word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In Radev and Mihalcea (2008) and Mihalcea and Radev (2011), an overview of network-based approaches is presented for a number of NLP problems. In Radev and Mihalcea (2008) and Mihalcea and Radev (2011), an overview of network-based approaches is presented for a number of NLP problems.…”
Section: Related Workmentioning
confidence: 99%
“…In Radev and Mihalcea (2008) and Mihalcea and Radev (2011), an overview of network-based approaches is presented for a number of NLP problems. In Radev and Mihalcea (2008) and Mihalcea and Radev (2011), an overview of network-based approaches is presented for a number of NLP problems.…”
Section: Related Workmentioning
confidence: 99%
“…Graph theory is a well-studied sub-discipline of mathematics, with a large body of results and a large number of efficient algorithms that operate on graphs [20,9]. Despite the various existing linguistic theories, which lead to different ways of viewing sentence structure and therefore syntactic analysis, most linguists agree today that at the heart of sentence structure are the relations among words [18].…”
Section: Graph-based Representations In Natural Language Generationmentioning
confidence: 99%
“…Using the graph-theoretic paradigm to study a complex system has often revealed hitherto unsuspected patterns in it. While graph-based representation of texts has been used for some time in natural language processing tasks, such as, text parsing, disambiguation and clustering [3], the approach based on the new science of complex networks often asks questions from a different perspective that can shed new light on the organization of linguistic structure. For example, networks constructed on the basis of co-occurrence of words in sentences have been seen to exhibit (a) the small-world effect, i.e., a small average distance between any pair of arbitrarily chosen words, and (b) a scale-free distribution of the number of words a given word is connected to (i.e., its degree) [4].…”
Section: Introductionmentioning
confidence: 99%